Effect of Pt catalyst on the condensable hydrocarbon content generated via food waste pyrolysis - Kim, Soosan; Lee, Chang Gu; Kim, Yong Tae; Kim, Ki Hyun; Lee, Jechan (Chemosphere, 2020)
A Pt catalyst supported on activated carbon (Pt/AC) was used for an environmentally friendly thermal treatment of food waste under an inert atmosphere (i.e., pyrolysis). This catalyst influenced the amounts of condensable hydrocarbons and noncondensable gases but not that of the solid remaining after the pyrolysis; in particular, it contributed to shifting the carbon distribution from the condensable hydrocarbons to the noncondensable gases for the food waste pyrolysis. Moreover, its use suppressed the generation of harmful chemical compounds, especially at high temperatures. For example, a Pt/AC-catalyzed pyrolysis at 700 °C produced about 4 times fewer benzene derivatives than the same treatment without a catalyst; this probably occurred because the Pt sites catalyzed the decyclization reaction and/or the free radical mechanism, which is dominant in the thermal cracking of carbon-containing feedstock. This study suggests that a Pt/AC-catalyzed pyrolysis would be a more environmentally benign food waste treatment method.
Keywords: Benzene derivatives; Carbon containing; Carbon distribution; Environmentally benign; Free radical mechanism; Hydrocarbon content; Inert atmospheres; Non-condensable gas; Catalysis; Food; Gases; Hot Temperature; Hydrocarbons; Platinum; Pyrolysis; Refuse Disposal; Catalyst; Food waste; Pyrolysis; Waste disposal; Waste management